2007
DOI: 10.1017/s0952523807070484
|View full text |Cite
|
Sign up to set email alerts
|

Early development of eye and retina in lanternfish larvae

Abstract: The morphological characteristics of the eyes and the retinae of lanternfish larvae of Lampanyctus crocodilus, Benthosema glaciale, and Myctophum punctatum were analyzed in pre-flexion, flexion, and post-flexion stages. Pre-flexion larvae of L. crocodilus, the species with the shallowest depth distribution, had spherical eyes located antero-laterally on a strongly laterally-compressed head, suggesting a forward binocular visual field. B. glaciale and M. punctatum larvae live deeper in the water column and had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 53 publications
3
22
0
Order By: Relevance
“…Every lanternfish species analyzed in this study possessed a pure‐rod retina. Although cone photoreceptors have been indentified in larval stages (Bozzano et al, ), our study confirmed their absence in adult myctophids. The contribution of rod outer segments to the entire retinal thickness ranged from 13% to 57% within the central part of the retina in this study.…”
Section: Discussionsupporting
confidence: 84%
“…Every lanternfish species analyzed in this study possessed a pure‐rod retina. Although cone photoreceptors have been indentified in larval stages (Bozzano et al, ), our study confirmed their absence in adult myctophids. The contribution of rod outer segments to the entire retinal thickness ranged from 13% to 57% within the central part of the retina in this study.…”
Section: Discussionsupporting
confidence: 84%
“…Nevertheless, cone photoreceptors have been retained in a few species occupying the deep ocean. Examples are the lantern fish, Lampanyctus crocodilus , Benthosema glaciale and Myctophum punctatum (members of the superorder Scopelomorpha), that possess a rod‐dominated retina but retain a few cones mainly distributed in the central retina (Bozzano et al. 2007).…”
Section: Molecular Changes In Photopigment Genes Associated With Deepmentioning
confidence: 99%
“…Myctophid larvae appear to be visual predators(Conley & Hopkins, 2004) and, since their eyes are not yet fully developed and functional for nocturnal conditions(Blaxter, 1968), day-time feeding is likely more successful. According to a morphological study of the eye structure in larvae of Lampanyctus crocodilus (Risso 1810),Benthosema glaciale (Reinhardt 1837) and Myctophum punctatumRafinesque 1810, the formation of cone photoreceptors in the central area of the retina during preflexion stage indicates an increased visual capacity in daylight conditions and that these structures were progressively lost during development, as the individuals shift to adult life in deeper waters(Bozzano et al, 2007). Diogenichthys atlanticus fed more frequently during daytime and the V T peak for D. laternatus at 2200 h, which consisted almost entirely of digested remains, suggests that this species fed mostly during the afternoon.…”
mentioning
confidence: 99%